Methicillin-Resistant Staphylococcus aureus in Commercial Swine Herds Is Associated with Disinfectant and Zinc Usage - Slifierz, Mackenzie Jonathan (Appl Environ Microbiol, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) originating from swine is concerning for public health, but an understanding of the emergence and persistence of MRSA in nursery herds is lacking. The aim of this study was to determine whether MRSA in nursery pigs is associated with particular herd-level parameters, including the use of antimicrobials, disinfectants, and heavy metals, which may be driving the selection and persistence of antimicrobial resistance. Nasal cultures for MRSA were completed for 390 pigs from 26 farms at the end of the suckling phase and again at 3 weeks postweaning. Herd-level information was collected, and a random subset of MRSA isolates was screened for resistance to zinc and quaternary ammonium compounds (QACs). Multivariate analysis revealed that in-feed concentrations of zinc (P < 0.001) and frequent disinfection of nursery pens (P < 0.001) are associated with MRSA shedding in nursery pigs. Furthermore, 62.5% (25/40) of MRSA isolates carried the zinc resistance gene czrC and demonstrated decreased susceptibility to zinc. All MRSA isolates carried at least 1 QAC resistance gene. The most common genotype was qacG qacH smr, which occurred in 32.5% (13/40) of isolates. Seven isolates (17.5%) demonstrated a significant tolerance to benzalkonium chloride, indicating a potential to survive commercial QAC exposure in the presence of organic matter. Overall, these findings indicate that high levels of in-feed zinc and QAC-based disinfectants are important drivers in the selection and persistence of MRSA in commercial swine herds, and these agents may be coselecting for other antimicrobial resistance genes.